Direct EPR detection of atomic nitrogen in an atmospheric nitrogen plasma jet. Issue 7 (11th February 2020) - Rostas, Arpad Mihai; Ledernez, Loic; Dietel, Lisa; Heidinger, Lorenz; Bergmann, Michael; Altenburger, Markus; Bruch, Richard; Urban, Gerald; Schleicher, Erik; Weber, Stefan
Abstract : A nitrogen plasma generated by a self-designed microplasma device was analyzed by cw and pulse EPR spectroscopy in real time. Nitrogen atoms were detected and characterized in terms of spectral widths, relaxation times and actual concentrations. Abstract : In this study, an atmospheric nitrogen plasma jet generated by a custom-built micro-plasma device was analyzed at room temperature by continuous wave and pulse EPR spectroscopy in real time. Transiently formed nitrogen atoms were detected without the necessity to use spin-traps or other reagents for their stabilization. In contrast to results from optical emission spectroscopy, only signals from the 4 S ground state of 14 N and 15 N could be detected. EPR data analysis revealed an isotropic g value of 1.9971 and isotropic hyperfine coupling constants of a ( 14 N) = (10.47 ± 0.02) MHz and a ( 15 N) = (14.69 ± 0.02) MHz. Moreover, lifetime and relaxation data could be determined; both are discussed in terms of spectral widths and actual concentrations of the transiently formed nitrogen species within the plasma jet. The data show that the lifetimes of atomic nitrogen and charged particles such as N + must be different, and for the latter below the observation time window of EPR spectroscopy. We demonstrate that the real-time (pulsed) EPR technique is a fast and reliable alternative to detect atomic nitrogen in atmospheric pressure plasma jets. The method may be used for a continuous monitoring of the quality of plasma jets.